Competency Development of Elementary School Teachers Through Lesson Study Implementation in the Independent Learning Curriculum - Susanto, Herry Agus; Suswandari, Meidawati; Kusumaningsih, Dewi; Mulyati, Sri (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The purpose of the research directed in this study was to determine the competence development of elementary school teachers through the implementation of lesson study in the independent learning curriculum. This type of research is quantitative descriptive. The population referred to in this study is a number of 243 teachers in SD N Sukoharjo Regency. The sample of this study were 28 elementary school teachers spread across Sukoharjo Regency. Sampling using cluster sampling. The data collection technique used in this research is observation. The weight for each question is measured through a Likert Scale. Data validity in the form of method triangulation. Descriptive analysis technique in the form of presenting data through tables or graphs. The findings show that when a teacher frees learning in learning, it is necessary to uphold competencies in every step of teaching. The first competency of the total observational assessment score is occupied by professional competence of 3.90, which is then followed by pedagogic competence of 3.78. Continuing on the third and fourth competencies, namely social competencies with a total of 2.80 and personality competencies with a total of 2.73. These four competencies play an important role in aligning the independent learning curriculum which is supported through the implementation of lesson study-based learning.